Przedstaw w postaci jednej potęgi i oblicz

a) [tex](\frac{1}{4})^{4} * 8^{4} =[/tex]

b) [tex]9^{2}/(\frac{3}{4})^{2}=[tex]


c)(-5)^{5}*2^{5}=[/tex]

d) [tex](-6)^{3}/(-3)^{3}=[/tex]

pls na jutro



Odpowiedź :

Odpowiedź:

Szczegółowe wyjaśnienie:

Zobacz obrazek Ela10557

Odpowiedź:

Szczegółowe wyjaśnienie:

[tex](\frac{1}{4})^4*(2^3)^4=4^{-4}*2^{12}=(2^2)^{-4}*2^{12}=2^{-8}*2^{12}=2^{4}=16[/tex]

[tex]\frac{9^2}{(\frac{3}{4})^2 }=(\frac{9}{\frac{3}{4}})^2=(\frac{9*4}{3})^2=(3*4)^2=12^2=144[/tex]

[tex]\frac{(-6)^3}{(-3)^3}=(\frac{6}{3})^3=2^3=8[/tex]

[tex](-5)^5*2^5=(-5*2)^5=(-10)^5=-100000[/tex]